2004
DOI: 10.1165/rcmb.2003-0373oc
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Receptor Antagonist Attenuates Airway Hyperresponsiveness Following Exposure to Ozone

Abstract: The role of an interleukin (IL)-1 receptor antagonist (IL-1Ra) on the development of airway hyperresponsiveness (AHR) and airway inflammation following acute O(3) exposure in mice was investigated. Exposure of C57/BL6 mice to O(3) at a concentration of 2.0 ppm or filtered air for 3 h resulted in increases in airway responsiveness to inhaled methacholine (MCh) 8 and 16 h after the exposure, and an increase in neutrophils in the bronchoalveolar lavage (BAL) fluid. IL-1beta expression, assessed by gene microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 45 publications
6
67
2
Order By: Relevance
“…Presence of functional AP-1 and NF-B binding sites in mouse MIP-2 (34, 53) and TNF-␣ (54, 55) gene promoters further supports TNF-mediated MIP-2 and TNF-␣ regulation via these transcription factors. The injurious effects of TNF-dependent IL-1␤ have also recently been determined after acute O 3 exposure (56). Interestingly, in the present study, IL-6 mRNA was overexpressed in O 3 -resistant Tnfr Ϫ/Ϫ mice, which may suggest a protective role for this cytokine.…”
Section: O 3 -Induced Hyperpermeability In Jnk1supporting
confidence: 60%
“…Presence of functional AP-1 and NF-B binding sites in mouse MIP-2 (34, 53) and TNF-␣ (54, 55) gene promoters further supports TNF-mediated MIP-2 and TNF-␣ regulation via these transcription factors. The injurious effects of TNF-dependent IL-1␤ have also recently been determined after acute O 3 exposure (56). Interestingly, in the present study, IL-6 mRNA was overexpressed in O 3 -resistant Tnfr Ϫ/Ϫ mice, which may suggest a protective role for this cytokine.…”
Section: O 3 -Induced Hyperpermeability In Jnk1supporting
confidence: 60%
“…Several studies identified an association between elevated levels of IL-1β and development of BPD or an adverse clinical outcome (6,9). An imbalance between IL-1β and IL-1Ra contributes to prolonged inflammation in BPD (11), and treatment with IL-1Ra protects from loss of function and structural damage in an ozone model of lung disease (35). Neonatal mice in which IL-1β was conditionally overexpressed in airway epithelial cells suffered from BPD-like disrupted alveolar septation and capillary growth and featured elevated levels of MIP-2 (8)-findings consistent with our data.…”
Section: Discussionmentioning
confidence: 99%
“…This response is abrogated when the product of the IL-1 receptor antagonist gene, IL-1Ra, competitively binds to the receptor but does not elicit the downstream signal transduction cascade. The pro-inflammatory effect of IL-1 and the antiinflammatory effect of IL-1Ra in asthma have been documented in a number of human and animal studies [9][10][11][12][13].…”
mentioning
confidence: 99%